Clues from Bariatric Surgery: Reversing Insulin Resistance to Heal the Heart - Khalaf, Khaled Imad (2013)
Obesity is a state of metabolic dysregulation of the whole organism and a major contributing factor to the epidemic of insulin resistant diabetes. The non-pharmacological treatment of obesity with bariatric surgery results in a dramatic and almost instantaneous reversal of insulin resistance. The present review collectively addresses the evidence for this phenomenon in the literature and discusses potential metabolic and neurohumoral mechanisms. We propose that nutrient restriction lowers the cell’s defense mechanisms for nutrient overload in insulin responsive organs.